Geogrid reinforcement mechanism and optimal design in ballast bed via DEM - Pan Tan; Yuanjie Xiao; Yiling Chen; Songtao Lv; Meng Wang; Yuqin Wang; Gulnaz Kanwal; Weidong Wang; Zhiwu Yu (Geotextiles and Geomembranes, 2026)

A tri-modal biosensor based on alkyne-functionalized gold nanoparticles and molecular beacon for detection of resistance-related point mutations in epidermal growth factor receptor-tyrosine kinase inhibitors - Ding Tan; Haixin Long; Ya Wang; Wenjing Lin; Yiling Huang; Haijun Chen; Yu Gao (Molecular Biology Reports, 2026)

​​Integrating machine learning and spatial transcriptomics uncovers shared immunomodulatory deubiquitinases in MAFLD and HCC - Yu-xi Han; Hongze Li; Wendi Xia; Junyi Ma; Jiaqi Zhang; Yiling Li (Human Genetics, 2026)

Ultrathin wide-bandgap niobate for high-performance photodetection and information encryption - Xiaoqiang Feng; Xiaolin Zhang; Ran Liu; Xiaolong Guo; Yuchan Hu; Lizhikun Gong; Yiling Yu; Lei Yin; Yao Wen; Yuchen Cai; Ruiqing Cheng; Jun He (Science Bulletin, 2026)

Direct functional recycling of waste polyester-cotton blended textiles into photothermal materials for solar-driven water evaporation and anti-icing/de-icing - Zijun Feng; Lan Bai; Jing Yu; Wenhao Xu; Chengfeng Shen; Yifan Liu; Yiling Wu; Shimei Xu; Yuzhong Wang (Chemical Engineering Journal, 2026)

Orderly regulation of amine-functionalized mesoporous silica SBA-15 to enhance the rapid adsorption and desorption of CO₂ - Leyu Nie; Yu Cheng; Wenqing An; Mingxuan Ren; Yiling Xu; Kai Xia; Zhaojun Chen; Deshuai Sun (Journal of Environmental Chemical Engineering, 2026)

2,2’-Biimidazole-based porous organic polymers for efficient capture of radioactive iodine at high temperature and low concentration - Zexing Ma; Chenjie Li; Siying Chen; Chunhui Zhou; Linhai Liu; Yiling Guo; Xiaolong Liu; Wenze Zhang; Song Tu; Jun Li; Xin Yu; Yaqiang Xie (Chemical Engineering Journal, 2026)

Generation and distribution of cyanide in rats and humans following sodium cyanoborohydride exposure - Zhenshuo Guo; Yiling Tang; Ruilin Zhang; Yu Ma; Ruxin Luo; Ping Xiang; Hui Yan; Wenjia Duan (Toxicology and Applied Pharmacology, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Spatiotemporal dependence of heavy precipitation on soil moisture anomalies in the Yangtze River Basin, China - Na Yang; Yiling Yue; Hang Yu; Li Zhang; Jun Yin; Junjie Gao; Yehui Zhang (Science of The Total Environment, 2025)

Time-space patterns of groundwater contamination in a closed MSW landfill: Insights from long-term monitoring and SOM-based clustering analysis - Jing-yu Peng; Shuai Zhang; Yujing Wang; Jiwu Lan; Shuairong Wang; Yiling Zhou; Linbo Wu; Liangtong Zhan (Environmental Pollution, 2025)

Structure characterization and biological activity of polysaccharides from Trametes sanguinea (TS-P) and wild Lentinus edodes (LE-P) - Ke Liu; Zheng-ao Sun; Xinlin Li; Xin Qing; Wen Yu; Mengnan Liu; Xiang Ding; Yiling Hou (Food Bioscience, 2025)

A multi-strategy self-adaptive differential evolution algorithm for assembly hybrid flowshop lot-streaming scheduling with component sharing - Yiling Lu; Qiuhua Tang; Shujun Yu; Lixin Cheng (Swarm and Evolutionary Computation, 2025)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Photocatalytic activation of oxalic acid over FeOOH loaded FeWO4/WO3 heterojunction for high-efficient degradation of tetracycline - Qingqing Chai; Jiahan Dong; Xiaofang Yu; Xiaoke Zhang; Jun Li; Sheng Guo; Yiling Yang (Journal of Environmental Chemical Engineering, 2024)

A near-infrared emitting “off-on” fluorescent probe for bioimaging of Pd(Ⅱ) ions in living cells and mice - Xiao-Fei Chen; Yu Song; Yiling Liu; Yang Zhou; Xin Zhao; Zifeng Yang (Analytica Chimica Acta, 2024)

Biodegradable cellulose/curcumin films with Janus structure for food packaging and freshness monitoring - Weiquan Wang; Xuewen Liu; Fan Guo; Yuxuan Yu; Jinqing Lu; Yiling Li; Qiaoyun Cheng; Jinping Peng; Goubin Yu (Carbohydrate Polymers, 2024)

Analysis of influencing factors and prediction of China’s Containerized Freight Index - Xiaoying Tu; Yiling Yang; Yu Lin; Shiqun Ma (Frontiers in Marine Science, 2023)
China, as a major maritime nation, the China Containerized Freight Index (CCFI) serves as an objective reflection of the Chinese shipping market and an important indicator for understanding China’s shipping industry globally. The shipping market is a complex ecosystem influenced by various factors, including vessel supply and demand, cargo supply and demand relationships and prices, fuel prices, and competition from substitute and complementary markets. To analyze and study the state of the Chinese shipping market, we selected the CCFI as an indicator and collected data on six factors that may affect the overall shipping market. These factors include “ the China Coastal Bulk Freight Index(CCBFI)”, “the Baltic Dry Index(BDI)”, “the Yangtze River Container Freight Index”, “Global: Aluminum (minimum purity of 99.5%, London Metal Exchange (LME) spot price): UK landed price”, “Major Ports: Container Throughput”, and “Coal Price: US Central Appalachia: Coal Spot Price Index”. Then, we constructed an analyticaland predictive framework using Deep Neural Network (DNN), CatBoost regression model, and robust regression model to study the CCFI. Based on the R 2 results of the three models, it is evident that DNN provides the best analytical and predictive performance for the CCFI, accurately forecasting its changes. Additionally, the robust regression model indicates that “Global: Aluminum (minimum purity of 99.5%, LME spot price): UK landed price” has the greatest impact on the CCFI. Finally, from a business perspective, we provide some suggestions for China’s container shipping industry.

More profound impact of CP ENSO on Australian spring rainfall in recent decades - Yiling Ma; Jilin Sun; Tianyun Dong; Weidong Yu; Wenjie Dong (Climate Dynamics, 2023)
Most of Australia was in severe drought from 2018 to early 2020. Here we link this drought to the Pacific and Indian Ocean sea surface temperature (SST) modes associated with Central Pacific (CP) El Niño–Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). Over the last 20 years, the occurrence frequency of CP El Niño has increased. This study extends the previous understanding of eastern Pacific (EP) El Niño-Australian rainfall teleconnections, exhibiting that CP El Niño can bring much broader and stronger rainfall deficiencies than EP El Niño during austral spring (September–November) over the northern Australia (NAU), central inland Australia and eastern Australia (EAU). The correlations between SST fields and rainfall in three Cluster regions divided by clustering analysis also confirm this, with rainfall variability in most of Australia except southern Australia (SAU) most significantly driven by CP ENSO. Also, we demonstrate that the CP El Niño affects rainfall in extratropical EAU via the Pacific-South American (PSA) pattern. While the influence of EP El Niño is only confined in tropical NAU because its PSA pattern sits far too east to convey its variability. With the development of ENSO diversity since 2000, the footprint of El Niño on Australian rainfall has become more complex.

Role of Natural resources rent on economic growth: Fresh empirical insight from selected developing economies - Yiling Yu (Resources Policy, 2023)

Challenging the limits of the oxygen balance of a pyrazole ring - Wenjin Zhang; Yiling Yang; Yuchuan Wang; Teng Fei; Yu Wang; Chenghui Sun; Siping Pang (Chemical Engineering Journal, 2023)

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Production of dissolved organic carbon in the South China Sea: A modeling study - Wentao Ma; Peng Xiu; Yi Yu; Yiling Zheng; Fei Chai (Science China Earth Sciences, 2022)

Nitrogen-cycling genes and rhizosphere microbial community with reduced nitrogen application in maize/soybean strip intercropping - Lingling Yu; Yiling Tang; Zhiguo Wang; Yonggang Gou; Jianwu Wang (Nutrient Cycling in Agroecosystems, 2019)

Overexpression of MeDREB1D confers tolerance to both drought and cold stresses in transgenic Arabidopsis - Yiling Yang; Wenbin Liao; Xiaoling Yu; Bin Wang; Ming Peng; Mengbin Ruan (Acta Physiologiae Plantarum, 2016)